2013
DOI: 10.5964/ijpr.v7i1.118
|View full text |Cite
|
Sign up to set email alerts
|

Shame and Guilt: Relationships of Test of Self-Conscious Affect Measures With Psychological Adjustment and Gender Differences in Iran

Abstract: In numerous studies conducted in Western societies, shame as measured by the Test of Self-Conscious Affect (TOSCA) has correlated with maladjustment whereas the TOSCA Guilt Scale has predicted adjustment. The present investigation sought to determine if such linkages would also appear in the Muslim cultural context of Iran. Iranian university students (N = 132) responded to Shame and Guilt Scales from the third version of the TOSCA, along with an array of personality measures. Shame correlated negatively with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 23 publications
3
5
2
1
Order By: Relevance
“…In parallel with Western data (e.g., Davis, 1983;Jonason, Lyons, Bethell, & Ross, 2013), men scored higher on narcissism, and women exhibited higher levels of both other-oriented empathy and empathic distress. While a previous Iranian study found that moral affects sometimes predict psychological functioning only in women (Ghorbani et al, 2013), this investigation failed to observe such outcomes, indicating that the operation of such effects may be limited. In short, attempts to explain why Iranian women failed to score higher on shame should be framed within an awareness that this one cultural difference occurred within the context of the many other similarities.…”
Section: Cultural Differencescontrasting
confidence: 90%
See 2 more Smart Citations
“…In parallel with Western data (e.g., Davis, 1983;Jonason, Lyons, Bethell, & Ross, 2013), men scored higher on narcissism, and women exhibited higher levels of both other-oriented empathy and empathic distress. While a previous Iranian study found that moral affects sometimes predict psychological functioning only in women (Ghorbani et al, 2013), this investigation failed to observe such outcomes, indicating that the operation of such effects may be limited. In short, attempts to explain why Iranian women failed to score higher on shame should be framed within an awareness that this one cultural difference occurred within the context of the many other similarities.…”
Section: Cultural Differencescontrasting
confidence: 90%
“…In the West, women score higher on both shame and guilt (Tangney & Dearing, 2002), but in this and in a previous Iranian study (Ghorbani et al, 2013), women scored higher only on guilt. This replicated effect, therefore, appeared to point toward a substantive cross-cultural contrast in the gender-related implications of shame.…”
Section: Cultural Differencescontrasting
confidence: 76%
See 1 more Smart Citation
“…Specifically, it was hypothesized that higher need for cognition would predict increased reflection (H1) and integrative self-knowledge (H2), and that reflection and integrative self-knowledge would be positively related to each other (H3). Positive associations between need for cognition, reflection, and integrative self-knowledge were previously reported by others (Ghorbani et al 2008 , 2013a , b ; Trapnell and Campbell 1999 ). It was also expected that those low in need for cognition would be more likely to be imbalanced in terms of assimilation (H4) and accommodation (H5).…”
Section: Introductionsupporting
confidence: 73%
“…Proceeding on the assumption that self-knowledge is a process organized in time, Ghorbani et al ( 2008 ) conceptualized integrative self-knowledge “as an adaptive and empowering attempt of the self to understand its experience across time to achieve desired outcomes” (p. 397). Research supports the benefits of integrative self-knowledge in enhancing mood and well-being while decreasing anxiety, depression, and various stress indicators (Ghorbani et al 2008 , 2013a , b ); and relates integrative self-knowledge to broad personality traits such as the Big Five (Tahmasb et al 2008 ).…”
Section: Introductionmentioning
confidence: 83%